1963
DOI: 10.1083/jcb.16.3.513
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Cytodifferentiation

Abstract: The cells of the anterior region of the larval fatbody of Drosophila melanogaster accumulate kynurenine at the end of the third larval instar, whereas the cells of the posterior region are involved in pteridine metabolism. Through a series of transplantation experiments it has been demonstrated that the anterior fat cells synthesize kynurenine. The mutant vermilion lacks kynurenine, and the anterior fat cells of this mutant strain lack the autofluorescence characteristic of kynurenine. When the non-allelic sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

1963
1963
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…This pattern of autofluorescence is also maintained when larvae are removed from food in the mid third instar and given only distilled water until they pupate. However, the number of fat cells containing kynurenine is increased when the larvae are fed tryptophan, as reported previously (12). For these earlier studies, L-tryptophan was dissolved in distilled water by slight heating.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…This pattern of autofluorescence is also maintained when larvae are removed from food in the mid third instar and given only distilled water until they pupate. However, the number of fat cells containing kynurenine is increased when the larvae are fed tryptophan, as reported previously (12). For these earlier studies, L-tryptophan was dissolved in distilled water by slight heating.…”
Section: Resultssupporting
confidence: 65%
“…Induction of kynurenine synthesis can also be achieved in Drosophila by feeding tryptophan to the larvae (14). In the latter instance, increased tryptophan pyrrolase activity is correlated with an increase in the number of cells in the fatbody which are producing kynurenine (12). The intracellular distribution of this metabolite in the larval fat cells can be conveniently determined by examination of this tissue with the fluorescence microscope, and it has been shown that the light blue autofluorescence characteristic of kynurenine is limited to the cells in the anterior region of the larval fatbody in the wild-type Ore-R strain of D. melanogaster.…”
mentioning
confidence: 99%
“…As described previously, "kynurenine cells" are in immediate contact with pteridine cells in the fatbody and diffusion of this metabolite from one region of the fatbody to another does not occur. A dietary supplement of tryptophan increases the quantity of kynurenine in the fatbody and examination with the fluorescence microscope reveals that the fluorescence characteristic of kynurenine is no longer limited to the anterior cells but is found in some posterior cells as well (12,13). It may be questioned whether, under these experimental conditions, the anterior cells produce larger quantities of kynurenine which then diffuse to other fat cells.…”
Section: Methodsmentioning
confidence: 99%
“…This regional localization of kynurenine synthesis is maintained when the larvae are fed yeast under the usual culture conditions or if the larvae are submitted to a brief period of starvation. Addition of tryptophan to the diet of third instar larvae increases kynurenine production in the fatbody with the result that a greater number of fat cells contain globular cytoplasmic inclusions displaying the characteristic light blue autofluorescence of kynurenine (12,13).…”
mentioning
confidence: 99%
“…Rizki (136) shows that only the cells of the anterior part of the larval fat body of Drosophila synthesize and accumulate kynurenine. In a normal strain, an extension of the number of cells containing kynurenine can be induced by feeding tryptophan, and cells which are normally differentiated for other synthesis (like pterins) may produce kynurenine as well.…”
mentioning
confidence: 99%